2021
DOI: 10.1007/s10792-021-01953-4
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-93-5p participates in type 2 diabetic retinopathy through targeting Sirt1

Abstract: Objective To investigate the role of miR-93-5p in rats with type 2 diabetic retinopathy (DR) through targeting Sirt1. Methods The targeting correlation between miR-93-5p and Sirt1 was validated by dual-luciferase reporter gene assay. Type 2 diabetes mellitus (T2DM) rat models were received intravitreal injection of antagomir NC (negative control), miR-93-5p antagomir, miR-93-5p agomir and/or recombinant Sirt1, followed by observation of pathological changes in retina via HE staining. Besides, retinal vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…In a study on miR‐93 and tumor growth factor‐β‐mediated epithelial–mesenchymal transition (EMT) pathway on arising retinal pigment epithelium‐19 (ARPE‐19) cells, EMT was found to be triggered in mesenchymal ARPE‐19 to epithelial transition (Fuchs et al, 2020 ). Moreover, a study on Type 2 diabetic retinopathy using qRT‐PCR and Western blot analysis demonstrated that while increasing the activity of antioxidative indicators, miR‐93‐5p inhibition downregulated VEGF levels and proinflammatory cytokines via Sirt1 overexpression, possibly through YAP/HIF1a/VEGFA pathway (H. Wang et al, 2021 ). MiR‐93 in glioma cell lines and glioma tissues was significantly upregulated, and it is correlated with clinicopathologic grading and survival in patients and may directly activate PI3K/Akt signaling by suppressing PTEN, PHLPP2, and FOXO3 expression targeting 3′‐untranslated regions (UTRs) (Jiang et al, 2015b ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study on miR‐93 and tumor growth factor‐β‐mediated epithelial–mesenchymal transition (EMT) pathway on arising retinal pigment epithelium‐19 (ARPE‐19) cells, EMT was found to be triggered in mesenchymal ARPE‐19 to epithelial transition (Fuchs et al, 2020 ). Moreover, a study on Type 2 diabetic retinopathy using qRT‐PCR and Western blot analysis demonstrated that while increasing the activity of antioxidative indicators, miR‐93‐5p inhibition downregulated VEGF levels and proinflammatory cytokines via Sirt1 overexpression, possibly through YAP/HIF1a/VEGFA pathway (H. Wang et al, 2021 ). MiR‐93 in glioma cell lines and glioma tissues was significantly upregulated, and it is correlated with clinicopathologic grading and survival in patients and may directly activate PI3K/Akt signaling by suppressing PTEN, PHLPP2, and FOXO3 expression targeting 3′‐untranslated regions (UTRs) (Jiang et al, 2015b ).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 156 ] identified a targeting relationship between miR-93–5p and SIRT1 using luciferase reporter gene assay. They found that miR-93–5p is upregulated and SIRT1 is downregulated in rats with DR.…”
Section: Micrornas Participate In Dr Development By Different Mechanismsmentioning
confidence: 99%
“…An investigation of the antioxidant activity of 25-hydroxyvitamin D3 (vitamin D) in human retinal endothelial cells revealed a reduction in miR-93 transcript with high glucose and vitamin D treatment, compared to high glucose alone, as well as reduced ROS production, malondialdehyde (MDA) content, and an increased level of reduced glutathione (GSH) [ 169 ]. Another investigation using a rat model of streptozotocin-induced diabetes indicated that miR-93 targeted sirtuin 1 (SIRT1) in the diabetic retina, inducing changes indicative of oxidative stress and inflammation which could be reversed by SIRT1 overexpression [ 170 ]. Several other miRNAs have recently been implicated in oxidative damage in diabetic retinopathy, including miR-1, miR-19a, and miR-320a repression of mitochondrial SIRT transcripts SIRT3, SIRT4, and SIRT5, respectively [ 171 ], miR-301a-3p regulation of six-transmembrane epithelial antigen of prostate 4 (STEAP4) expression [ 172 ], and miR-338-3p negative regulation of glutamine transporter SLC1A5 expression, leading to ferroptosis [ 173 ].…”
Section: Regulation Of Oxidative Stress By Non-coding Rnamentioning
confidence: 99%